Cost of element for fire protection system in school buildings / Siti Nadhirah Rosli and Norfashiha Hashim - Rosli, Siti Nadhirah; Hashim, Norfashiha (2018)
Construction industry is considered as one of the most important industries in Malaysia. It is well known that cost overrun is a typical problem that occurs in construction industries. Therefore, this phenomenon may affect the progress of construction industry as well as may reveal many institutions of construction to be destroyed. This study focuses to analyse the cost of each element of fire protection system . The objectives of this research are to extract the element of active fire protection system, to investigate the cost of element of active fire protection system and to determine the factor that influences the cost of element of active fire protection system . The scope of this research focuses on the active fire protection system in school building at SMK Orkid Desa, Smk Seri Sentosa and SMK Petaling, Kuala Lumpur. All the data utilized in this research are gathered from contract documents, previous researches, published articles and supported by an interview session among contractors of school building. Results of the analysis indicate that not all of the elements are installed in the school building. Besides, the costs of element in each case study and factor that influences the cost are different from one to another.